LOVE in the time of Covid-19: a brief mental health intervention to overcome loneliness. (October 2021) - Kar Ray, Manaan; Chow, Ka Ki; Theodoros, Theo; Wyder, Marianne; Steginga, Anne; Sorrensen, Rosemary; Hickey, Paul; Lau, Geoff; Kinsella, Kieran; Lombardo, Chiara
Objective: The coronavirus disease 2019 outbreak and its containment through public health strategies has resulted in a parallel pandemic of psychological distress. Increased loneliness and social isolation are associated with adverse health outcomes, yet there is a gap in brief interventions that specifically target loneliness. This article introduces a brief intervention to strengthen connectedness, LOVE. In a systematic way, this solution-focused approach encourages openness and sharing of current struggles with the existing circle of support. There are four steps in LOVE:L ist people in one's life, O rganise them on the helpfulness–availability matrix, V erify what they know to map them onto circles of trust andE ngage them through self-disclosure. Conclusion: The article details each concept, its importance, the pragmatics involved and top tips to guide practice. The memorable acronym provides logical sequence and structure. It is time efficient in training and delivery, with no former mental health knowledge required so there is potential for wide application. It facilitates collaboration between health professionals and people in distress and promotes empowerment and self-resilience. Adapted from the safety planning component of PROTECT, a pre-existing suicide prevention framework, LOVE has to be fine-tuned as a brief intervention in the wider context of the pandemic.